Assessing the effect of soil parameterization in land use change impact modeling - Yira, Yacouba; Bossa, Yaovi Aymar; Amoussou, Ernest; BADOU, D. Félicien; Hounkpè, Jean; Hounkpatin, Kpade Ozias Laurentin (My University, 2021)
This study addresses the importance of integrating the effect of land use on soil infiltration rate into land use change impact modeling. Based on a validated version 9.05.04 of the Water balance Simulation Model-WaSiM (statistical quality measures > 0.7), and field measurement of the infiltration rate under cropland and fallow, sixteen model simulations were performed. The impact of land use change is computed comparing LULC status of years 1990 and 2013. The effect of soil parameterization is computed using a refined soil map integrating land use change impact of soil infiltration rate and a classic soil map not considering this interaction. The results show differences in model results as an effect of soil parameterization approaches, indicating that the model is sensitive to the integration of LULC related effects on soil hydraulic conductivity. These differences are more pronounced with increasing modeling time steps (24 and 28 h). The signal-to-noise-ratio indicates that, results achieved in LULC impact assessment with a classic and a refined soil parameterization are very comparable except for interflow.
Keywords: Soil infiltration; soil hydraulic conductivity; Water balance simulation; Model-WaSiM